2000
DOI: 10.1080/j.1440-1614.2000.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Suicide and Attempted Suicide among Young Australians

Abstract: While much is known about the epidemiology of youth suicide, much remains to be clarified. Study of indigenous issues is perhaps the most neglected area; study of family issues may be potentially be the most productive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 105 publications
2
54
0
Order By: Relevance
“…Data were categorised into five year age groups from 15-19 years to >80 years. Given the variable classification protocols over time, biases may exist in Australian suicide data, 39 but it has been observed that the magnitude of such biases do not preclude the use of suicide data for aggregate or secular analyses. 40 Estimates of national GDP provided by Butlin 41 were used to calculate the per cent annual GDP change for the period under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…Data were categorised into five year age groups from 15-19 years to >80 years. Given the variable classification protocols over time, biases may exist in Australian suicide data, 39 but it has been observed that the magnitude of such biases do not preclude the use of suicide data for aggregate or secular analyses. 40 Estimates of national GDP provided by Butlin 41 were used to calculate the per cent annual GDP change for the period under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…While girls report suicidal thoughts more often than boys during adolescence,25 26 completed suicide in adolescence and young adulthood is 3–4 times more common in males than females in the Western World 25 27 28. The prevalence of suicidal thoughts among girls peaks at about 16 years of age, while it continues to increase beyond the age of 19 in boys 29.…”
Section: Introductionmentioning
confidence: 99%
“…An urban–rural disparity in children’s suicidal ideation has been previously reported in young people in China [19-22], however, the direction of this disparity has been inconsistent between studies. Inconsistent conclusions about the direction of urban–rural disparities in children’s suicidal ideation may have resulted from comparisons of results from different cross-sectional surveys (with possible differences in study design), rather than a comparison of rates between areas in the one study [4]. The results of the present study that has used longitudinal data to capture changes in children’s suicidal ideation over time in urban and rural areas are therefore extremely valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is among the 8th to 10th leading causes of death in those aged 5–14 years [3]. However, as suicide is rarely reported in children under 14 years of age, suicide in this age group is likely to be underestimated [4]. …”
Section: Introductionmentioning
confidence: 99%